Augmented reality application: enhancing visitor experience at the Sabah State Museum / Mohd Darnish Syahmi Mhd Yatim ... [et al.] - Mohd Yatim, Mohd Darnish Syahmi; Rabusah, Nur Sabrina; Omar, Aaqilah; Gatu, Alvin; Mohamad Musa, Nurafiqah; Mohd Zaidi, Nur Murniza (Universiti Teknologi MARA, Sabah, 2022)
Advancements in technology and its merging with tourism is making travel a more pleasurable and memorable experience. Now, more than ever, travelers and visitors can enjoy visiting places with the use of technical apparatus and the internet. The development and advancement of Augmented Reality (AR) in tourism enables people to use digital visual components, sound, or other sensory stimulation transmitted via technology to create an improved version of the real physical world. Hence, the purpose of this study is to examine the effects of Augmented Reality in augmenting the experiences of visitors to the Sabah State Museum specifically in terms of learning outcomes, entertainment experiences, and expectations met. The study applied a quantitative approach and analysis that focused on visitors to the museum who reside in Kota Kinabalu. Through purposive sampling technique and cross-sectional data collection, 388 responses met the requirements of the survey and were used for data analysis. Data was collected via Google Form while the survey questionnaire was adopted from various previous studies with some modifications. Based on the results, the learning outcomes significantly affected the visitor experience as AR was instrumental in increasing the learning outcome. In addition, it was found that using AR features attracted visitors to learn more using the technology provided by the museum. As for the entertainment experience, the results of the study also showed a positive effect of the usage of AR on the visitors’ experience in the museum. Thus, the findings have important contributions particularly how AR can enhance the visitors’ experience at the Sabah State Museum.